The Influence Of The Number Of Commodity Types And Storability On The Sales Level Of Hydroponic Vegetable Producers - Ewiel, Ewiel; Miftah, Himmatul; Novita, Ita (Universitas Djuanda, 2024)
As the number of hydroponic vegetable producers in Bogor City increases, producers must improve strategies and win the competition to stay ahead. This study aims to determine how the sales level of hydroponic vegetable producers in Bogor City, how the number of commodity types and shelf life of hydroponic vegetable producers in Bogor City and the effect of the number of commodity types and shelf life on the sales level of hydroponic vegetables in Bogor City. This research was conducted in May-June 2023. The data collection method was carried out by census. Respondents in this study were 20 hydroponic vegetable businesses. Data analysis used descriptive analysis, quantitative analysis and multiple linear regression analysis. Descriptive analysis and quantitative analysis to answer objectives one and two, namely at the most dominant sales level 8 companies sell vegetables as much as 101-500 kg / month, while the least sales are 1 company selling vegetables less than 50 kg / month. The most dominant number of vegetable commodities 8 companies have 3-4 types of vegetables, the most dominant shelf life 11 companies with vegetable shelf life 4-6 days. Then in multiple linear regression analysis using SPSS version 24, it was found that the significant effect on the variable number of commodity types and storability (X) on the level of sales (Y) was marked by the value of t count > from t table, f count > from f table and obtained a coefficient of determination R2 of 80.4% while the remaining 19.6% was influenced by other variables not carried out in this study.